Risk factors of digital dermatitis in feedlot cattle. Issue 3 (13th May 2021) - Cortes, Julian A; Thomas, Anice; Hendrick, Steve; Janzen, Eugene; Pajor, Ed A; Orsel, Karin
Abstract: Digital dermatitis (DD ) has been reported in North American feedlots, although risk factors are not well characterized. Our objectives were to analyze: (1) foot and leg conformation and (2) pen hygiene, as potential variables that predispose feedlot cattle to DD. Production parameters in DD-affected cattle were compared with healthy cattle and with those diagnosed with more commonly known infectious lesion foot rot (FR ). In total, 2, 854 feedlot cattle in 11 pens in 2 feedlots were assessed (bi-weekly pen walks) throughout the feeding cycle. Pen condition was categorized as: "dry, " "mud present but has good bedding, " "more mud than bedding, " and "excessive mud." Gait scoring was competed and cattle with abnormal gait or evident foot lesions (i.e., DD or FR) were restrained in a cattle chute for a close foot inspection ( n =280), including scoring of foot angle and claw set and hind and side views of rear feet and legs. Cumulative incidence of DD (present or absent) and FR was 2.5% (71/2, 854) and 11.6% (331/2, 854), respectively. Foot and leg conformation was not significantly different between left and right sides or between cattle with ( n =71) and without DD ( n =209). Lameness was diagnosed in only 22% of cattle with DD. Cattle with DD gained 0.27 kg/d less compared with healthy cattle (mean ± SD: 1.29 ± 0.29 vs. 1.56 ± 0.27, P <0.05) and 0.4 kg/d less compared with FR (1.29 ± 0.29 vs. 1.69 ± 0.25). Presence of DD was not significantly different between pens with "dry" and "mud present but has good bedding, " but for pens with "more mud than bedding" or "excessive mud, " the risk of cattle having DD cases increased significantly [odds ratio (OR )=8.55, confidence interval (CI ): 4.0–18.4 and OR=14.1, CI: 5.9–33.8, respectively]. In conclusion, it is important to keep good pen conditions to reduce the risk of DD, which can be managed through proper stocking density and strategic bedding, irrespective of foot and leg conformation.